The Mediation of Critical Themes of Motherhood Studies in Storytelling: The Case of The Girl Who Drank the Moon - Millan Scheiding, Catalina (Cuestiones de Género: de la igualdad y la diferencia, 2024)
By contemplating the emotional and intellectual link between the reader and the book, this article considers how a contemporary text might respond to current motherhood studies’ issues, and how these studies are mediated to be considered appropriate for an audience of young readers. A psychosocial research strategy is used, through a feminist theoretical framework, to analyze how the young adult novel The Girl Who Drank the Moon incorporates key ideas of motherhood studies through characters’ agency and the storytelling arch. Motherhood is represented as an institution, an individual identity and an emotional experience, and the novel offers the young reader a nuanced vision into an ongoing discussion. The potential of storytelling to mediate social justice concerns to the young reader is highlighted.